Apex Resection and Retrograde Filling After Enucleation of Radicular Cyst : A Case Report - Teuku Ahmad Arbi; Abdul Latif (Cakradonya Dental Journal, 2013)
Radicular cyst is a cyst at the apex of a non-vital tooth and is a sequel of pulp inflammation. The associated tooth is usually asymptomatic. Acute infectious episodes may cause pain. The lesion appears as a sharply circumscribed radiolucent lesion around the apex of the associated tooth. Several treatment options exist for such cysts. Many small cysts resolve with endodontic therapy (root canal treatment) of the involved tooth. Those lesions should be monitored to ensure such resolution. Cysts that fail to resolve with such therapy should be surgically removed. This is often accompanied by an apex resection of the tooth involved. This entails cutting off the end of the tooth and sealing, preventing the leakage of root canal filling. We present a case of Indonesian female, 24 years old with radicular cyst at second left maxillary incisor. The teeth was already performed root canal treatment, but the cyst did not decreased in size and the teeth was mobile. We decided to perform enucleation and apex resection of involved teeth. A mucoperiosteal flap over the cyst is raised a window is opened in the bone to give adequate access. The cyst is carefully separated from its bony wall. The entire cyst is removed intact. The apex was cutting off 3 mm and MTA was place at the orifice of the root. The edge of bony cavity are smoothened off, free bleeding is controlled and cavity is irrigated to remove debris. Mucoperiosteal flap is replaced back and sutured in place. Three weeks after surgery, the patient has no complain on operation area, the tooth was not mobile and no pain. Radiographic evaluation shows that the operation area is healing successfully.